Peran Harga Terhadap Kepuasan Pelanggan Pada Erigo Di E-Commerce Shopee - Alya Takwarina Cahyani; Slamet Riyono; Wahyu Wirasati (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Erigo is an Indonesian fashion brand since 2003 that sells various types of clothing products. Erigo is one of the largest local brands that has many customers. This research was conducted to determine the effect of price, product quality and Erigo customer satisfaction on Shopee e-commerce. There were 51 respondents as Erigo customers on Shopee e-commerce. This research uses the cross table analysis method and hypothesis testing using the product moment correlation formula. Through hypothesis testing, there is a strong influence between price and Erigo customer satisfaction on Shopee e-commerce. Then there is a strong influence between product quality and Erigo customer satisfaction at e-commerce Shopee. Meanwhile, in the last hypothesis, there is no simultaneous influence between price and product quality on Erigo customer satisfaction at Shopee e-commerce. The advice that can be given is that it is hoped that Erigo maintains affordable prices by continuing to improve product quality so that customers remain satisfied when buying Erigo on Shopee e-commerce.